Problemas no ajuste da curva de crescimento do pacu, Piaractus mesopotamicus (Holmberg, 1887) (Pisces: Characidae), e seu manejo no Pantanal Mato-Grossense - Vaz, Mônica Maria [UNESP] (2001)
Fish growth studies are fundamental in stock management. The pacu or pacucaranha, Piaractus mesopotamicus (Holmberg, 1887), has great fishing importance in the Pantanal of Mato Grosso, Brazil. Fish samples were obtained in the municipal market of Cuiabá/MT, from April/94 to June/95. The fish were weighed, measured and scales were extracted for age determination. At spawning period, when possible, it was identified the sex of some larger individuals. For age determination, rings in scales were counted, the distances between the nucleus and each ring, and between the nucleus and the border of the scale, were measured. Through the marginal increment analysis it was possible to identified that 2 rings are annually formed, one in September/94 (dry season) and another in February/95 (wet season), coinciding with the reproductive and the trophic migrations periods, respectively. The SCHNUTE and the von BERTALANFFY models, both tested by the non-linear regression, utilizing the data of average standard length for each age, did not converge for biologically plausible values. In relation to the back-calculation, the model that showed better adjustment to the observed data was the BPH (Body Proportional Hypothesis). The length frequency distribution, analyzed by FiSAT (ELEFAN I), was appropriated to the estimative of the growth parameters, resulting in: LS¥ = 86 cm; k = 0.48 year-1, indicating a comparatively fast growth. An analytical simulation obtained by the method proposed by BEVERTON; HOLT resulted in F1994/1995 = 0.955 year-1; and FMSY = 1.0 year-1 (when M = 0.78 year-1), showing that this freshwater fish species population is close to its maximal sustainable yield. The index of growth performance (f') was estimated in 3.55. A longevity (A0.95) resulted in 4.69 years, indicates a short life cycle, with t0 equal to -1.55 years. The annual survival rate (S) was estimated in 17.64%